Draft Sixth Five Year Plan 1980-85 Part II - Planning Commission, Government of India (Planning Commission, Government of India, 1981)
The agricultural growth pattern during the Sixth Plan period has to take into account the immediate as well as the long-term needs for agricultural commodities both for domestic consumption and for export. The highest priority will be accorded to bridging the gap prevailing between actual and potential farm yields even at current levels of technology through the removal of the constraints responsible for this gap. The napped yield reservoir is quite high in most of the farming systems in the country and there by serves as a source of optimism for achieving accelerated growth. Both agricultural and fisheries will have to receive concurrent attention through the development of appropriate packages of technology, services and public policies, which can help to enhance production from the soil as well as the sea and there by improve the income of farmers and fishermen.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Agriculture and Allied Activities; Economic development; Command Area Development and Flood Control; Rural Development; Village and Shall Industries; Manpower and Employment; Minimum Needs Programme; Communications Information and Broadcasting; Sixth Five Year Plan- India